Role of disulfidptosis in colorectal adenocarcinoma: implications for prognosis and immunity - Yang, Ruanruan; Lai, Chunxiao; Huang, Luji; Li, Feng; Peng, Weiqi; Wu, Meiyan; Xin, Jinge; Lu, Yan; Ouyang, Manzhao; Bai, Yang; Lei, Haoqiang; He, Shunhui; et al. (Frontiers in Immunology, 2024)
Colorectal cancer is one of the common malignant tumors worldwide, and early detection and diagnosis are crucial for improving the prognosis of patients with colorectal cancer. Recent research has found a new way of cell death: disulfidptosis.Under glucose starvation, abnormal accumulation of disulfide molecules such as Cystine in SLC7A11 overexpression cells induced disulfide stress to trigger cell death.The research on disulfidptosis is still in its early stages, and its role in disease progression is still unclear.In this study, we used a public database to detect the expression and mutations of disulfidptosis-related genes in COAD. We conducted clustering analysis based on disulfidptosis-related genes and analyzed differentially expressed disulfidptosis-related genes. A prognostic risk model was built using 7 disulfidptosis-related genes, and the reasons for prognostic differences were explored through immune infiltration analysis and drug sensitivity analysis. Finally, the expression of key genes were validated in clinical samples. Our research findings provide evidence for the role of disulfidptosis in COAD and offer new insights for personalized and precise treatment of COAD.